The Bipolar Hip: Combined Acetabular and Femoral Pathomorphology Determine Hip Motion. Issue 7 (29th July 2019) - Shin, Jessica; Adeyemi, Temitope F.; Hobson, Taylor; Peters, Christopher L.; Maak, Travis G.
Objectives: Prior studies have suggested femoral version may outweigh the effect of cam impingement on hip internal rotation; however, the effects of acetabular morphology were considered. This study investigates the influences of acetabular and femoral morphology on hip range of motion (ROM) in patients with femoroacetabular impingement syndrome (FAIS). Methods: With IRB approval, a retrospective chart review and radiographic analysis was performed of patients presenting with hip pain to the clinic of a single surgeon. Patients were included in the study if their hip pain was thought to be intra-articular in origin, had full physical exam documentation (including bilateral hip evaluations and measurements of passive hip ROM), Tönnis grade ≤ 1, and had full imaging including: AP pelvis, 45⁰ Dunn lateral, and false profile radiographs and a CT scan with 3-D reconstructions of the affected hip. Patients were excluded if they had prior hip surgery, prior hip trauma or other underlying hip pathology. Femoral head/neck angle, femoral version, size and clock-face location of the maximum femoral alpha angle, mid-coronal center edge angle (CEA), mid-sagittal CEA, acetabular version at the 1, 2 and 3 o'clock positions and the McKibbin index were measured on CT scan. Univariable and multivariable logistic regression analyses were performed to determine which measurements correlated with hip ROM. Results: 200 hips from 200 patients were included in the final analysis. Mean age was 31.9 ±10 years, 145 (72%) patients were female, and mean BMI of the cohort was 25.2 ± 5. Univariable logistic regression analysis found femoral head/neck angle, mid-sagittal CEA, acetabular version at 1 and 2 o'clock, and McKibbin Index all significantly correlated with hip flexion (all q's > 0.05 after adjusting for false discovery rate). Femoral head-neck angle, femoral version, and McKibbin index all significantly correlated with external rotation. Femoral neck version, mid-sagittal CEA, acetabular version at all three clock positions, McKibbin index, max femoral alpha angle, and alpha position all significantly correlated with internal rotation. In the multivariate logistic regression analysis mid-sagittal CEA was the only measurement correlating with flexion, femoral head/neck angle and McKibbin index were the only significant variables correlating with external rotation, and McKibbin index and maximum femoral alpha angle were the only variables correlating with internal rotation. The results of the logistic regressions are summarized in Figure 1. Conclusion: Our univariate data supported previous data that suggested femoral version significantly correlated with hip internal rotation. However, multivariate analysis including acetabular version demonstrated that combined acetabular and femoral version significantly correlated with internal and external rotation while femoral version in isolation did not. In contrast to prior studies, an increased cam deformity, as defined by max femoral alpha angle, remained a significant contributor to reduced internal rotation but did not affect hip flexion. Rather, the increased mid-sagittal CEA remained the sole significant contributor to reduced hip flexion in the multivariable analysis. These data suggest that hip ROM is affected in a bipolar fashion and careful multiplanar evaluation of the femoral and acetabular pathomorpohlogy should be conducted prior to attempting to increase hip ROM with corrective osteoplasty or osteotomy. Figure 1. Association between CT variables and range of motion from univariable and multivariable regression *q-values are p-values adjusted for false discover rate. ‡In the multivariable logistic regression analysis, only 1 variable of the highly correlated CT measures were include.